A new 12% chromium steel strengthened by Z-phase precipitates. (1st March 2016) - Liu, Fang; Rashidi, Masoud; Johansson, Lennart; Hald, John; Andrén, Hans-Olof
Abstract: In order to increase the corrosion resistance and simultaneously maintain the creep resistance of 9–12% Cr steels at 650 °C, a new alloy design concept was proposed, using thermodynamically stable Z-phase (CrTaN) precipitates to strengthen the steel. A new trial Z-phase strengthened 12% Cr steel was produced and creep tested. The steel exhibited good long-term creep resistance. Dense nano-sized Z-phase precipitates were formed at an early stage, and coarsened slowly. They remained small after more than 10, 000 h. Graphical abstract: